Analysis of package inserts of orally administered drugs available in the Indian market - Chhaya, Maheshi U. (International Journal of Research in Medical Sciences, 2017)
Background: The package insert of a medication forms an important source of information to the patient while taking a drug. The package insert is expected to contain complete information regarding the drug aiding the patient to obtain additional knowledge regarding the drug. Methods: 100 package inserts of orally administered drugs were obtained from local chemists and were analysed according to the Sections 6.2 and 6.3 of Schedule D (II), Drugs and Cosmetics Act (1940) and Rules (1945). Results: The posology and contraindications were mentioned in 98% and 96% of the inserts, respectively, whereas the list of excipients, incompatibilities and shelf life was mentioned in 12%, 19%, 16% of the inserts, respectively. Conclusions: There is a wide variation in the information available on the package inserts of drugs available in the Indian market. The package inserts should be carefully scrutinized for completeness before the respective drug is marketed.